2012
DOI: 10.1111/evo.12015
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Locomotor Rhythmicity in Tetrapods

Abstract: Differences in rhythmicity (relative variance in cycle period) among mammal, fish, and lizard feeding systems have been hypothesized to be associated with differences in their sensorimotor control systems. We tested this hypothesis by examining whether the locomotion of tachymetabolic tetrapods (birds and mammals) is more rhythmic than that of bradymetabolic tetrapods (lizards, alligators, turtles, salamanders). Species averages of intraindividual coefficients of variation in cycle period were compared while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 71 publications
0
44
0
Order By: Relevance
“…The resulting compression of the humeral head against the glenoid fossa has been shown to be an important source of dynamic stability in ball-and-socket glenohumeral joints (Lippitt & Matsen, 1993;Hsu et al, 2011), and is thought to be particularly important in intermediate poses of the shoulder when the capsule and ligaments are relaxed and unable to contribute to joint stability. The greater PCSAs of the m. supraspinatus and m. infraspinatus could thus serve to stabilize the humerus as it undergoes the rapid, rhythmic oscillations generated by the highly-tuned therian neuromuscular system (Jenkins & Goslow, 1983;Ross et al, 2013). By comparison, the smaller PCSA and longer fascicles of m. supracoracoideus may reflect a greater reliance by other amniotes on ligaments rather than muscle force (Haines, 1952) to stabilize the shoulder, and may facilitate protraction of the humerus as it moves through the long, horizontal arcs typical of "sprawling" locomotion (Jenkins & Goslow, 1983;Baier & Gatesy, 2013).…”
Section: Anatomical Differences Reflect Locomotor Transformationmentioning
confidence: 99%
“…The resulting compression of the humeral head against the glenoid fossa has been shown to be an important source of dynamic stability in ball-and-socket glenohumeral joints (Lippitt & Matsen, 1993;Hsu et al, 2011), and is thought to be particularly important in intermediate poses of the shoulder when the capsule and ligaments are relaxed and unable to contribute to joint stability. The greater PCSAs of the m. supraspinatus and m. infraspinatus could thus serve to stabilize the humerus as it undergoes the rapid, rhythmic oscillations generated by the highly-tuned therian neuromuscular system (Jenkins & Goslow, 1983;Ross et al, 2013). By comparison, the smaller PCSA and longer fascicles of m. supracoracoideus may reflect a greater reliance by other amniotes on ligaments rather than muscle force (Haines, 1952) to stabilize the shoulder, and may facilitate protraction of the humerus as it moves through the long, horizontal arcs typical of "sprawling" locomotion (Jenkins & Goslow, 1983;Baier & Gatesy, 2013).…”
Section: Anatomical Differences Reflect Locomotor Transformationmentioning
confidence: 99%
“…This is probably because primates cannot feed faster than their gasrointestinal tracts digest and pass food, so that digestive strategy (fast passage and inefficient extraction versus slow passage and efficient extraction) may be the limiting factor of daily feeding time . Thus, unlike the locomotor system, where the ability to move the musculoskeletal components at a range of frequencies is an important aspect of system performance, primate feeding systems appear to be optimized to operate within a relatively narrow frequency band . Indeed, they may even modulate the ingested bite size with food type so they can operate within this frequency band, thereby avoiding fatigue …”
Section: Primates Are Not Optimized To Eat Fastmentioning
confidence: 99%
“…While there are many metrics that can be used to represent inter-stride variability, we elected to use variability in stride cycle duration as our proxy as it is simple to replicate and has been shown to have important biomechanical consequences for gait stability [32,33]. At each speed interval (electronic supplementary material, table S2) for each individual Virginia opossum and tufted capuchin, we chose 30 strides at random and calculated the stride duration mean and standard deviation.…”
Section: (B) Preferred Transition Speed and Inter-stride Variationmentioning
confidence: 99%
“…Sensorimotor feedback about these unstable conditions could help guide the animal to a new stable locomotor state [24,26,[35][36][37]. In this dynamical systems context, it has been suggested that gait transitions serve to reduce locomotor variability and avoid unstable states that might lead to injury or unnecessary energy expenditure trying to avoid tripping and falling [3,9,19,[25][26][27]30,33].…”
Section: Introductionmentioning
confidence: 99%